Contextualizing Childhoods Growing Up in Europe and North America - Frankel, Sam; McNamee, Sally (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection draws together a variety of contexts of contemporary childhoods, linking thinking from Canada with spaces in the UK and Sweden. The contributors explores the discourses that shape those childhoods and how this then impacts on the way that children come to experience their everyday lives. The aim of the book is not to reflect the entirety of childhood experience but to draw off particular expertise that shine a light into partial, yet significant areas of children's lives, with the contributions engaging with a range of voices and perspectives. As a result, the collection advocates the need for childhood studies to zoom out from a predisposition to isolate the child, which has been seen as a necessary part of conceptualizing childhood. As a result, the book focuses on a 'context' for childhoods through a consideration of both structure and agency, and through this seeks to recognise the interconnected nature of the arenas within which children live theireveryday lives. A range of themes are covered, including the education system, identity within the home, suicide in communities, and younger children's 'political' engagement and sense of belonging. Contextualising Childhoods will be of interest to students and scholars across a range of disciplines, including sociology, law, and education.